Rekonstruksi Perlindungan Hukum Hak Penguasaan Tanah Dan Bangunan Di Kawasan Sempadan Sungai - Utomo, Setyo; Wagner, Ivan; Pratama, Erwin Aditya; Siswanto (Diktum: Jurnal Ilmu Hukum, 2022)
The need for land for every human being is one of the basic rights that should be fulfilled by the State. But in the empirical fact that happens there is a small part of the community who owns most of the existing land, on the contrary most of the members of the community who only owns land on a small scale and even do not own the land. Government as the embodiment of the State should try how to make justice in land ownership for all citizens can be realized. The objective to be achieved in writing this scientific paper is that the human rights of every citizen to the needs of the land can be fulfilled. The writing method used in this scientific paper is descriptive method of analysis. The conclusion of the writing of this scientific paper is the redistribution of land as part of land reform is one effort that can be done by the Government in the fulfillment of the human rights of every citizen in the fulfillment of land ownership. The government should not hesitate to redistribute the land for the needy to get the land considering some of the existing legal umbrella allows for it